The Internalization Effort of Student Scientific Attitude through Inductive Teaching Method in Basic Physics Practical Course, Biology Study Program - PMIPA FKIP UR - Zulhelmi, Zulhelmi; Nur, Muhammad (FKIP-Universitas Riau, 2017)
The purpose of this study is to know the internalizationimprovement of scientific attitude of Biology Education Student - PMIPAFKIP UR through the application of Inductive Teaching Methods in theBasic Physics Practical course. The approach used in this study was aClassroom Action Research (CAR) with cyclic pattern which consists ofplanning, implementation, observation and reflection. After two timeactions, the results of the assessment of the scientific attitude of the studentsincreased from 28.46% to 51.50% in cycle 1 and to 79.96% in cycle 2. Ingeneral, the indicator scientific attitude has been quite embedded in students.Assessment of student activity increased from 12.56% to 65.50% in cycle 1and to 78.06% in cycle 2. This result shows that the learning activity byapplying the Inductive Teaching Methods has been understood by thestudents. Assessment on student performance in the implementation of thelab also increased, from the average of 80.55% in cycle 1 to 81.87% in cycle2. Based on the results of the analysis, it can be concluded that through theapplication of inductive Teaching Methods in the Basic Physics Practicalcourse in Biology Education Study Program PMIPA FKIP UR canescalation the internalize scientific attitude of student.